A unity power factor current injection technique for three phase controlled bridge rectifier - Eka Firmansyah (2008)
Over the last decade, power electronic converters are widely applied in industrial, commercial, residential, aerospace, utility, and military applications. Several factors like lightweight, compact size, low-cost, compatibility with digital control, and energy saving, support the widespread of it application.